ANÁLISE RÁPIDA DE CARBONO ORGÂNICO E MATÉRIA ORGÂNICA EM SOLOS UTILIZANDO FLUORESCÊNCIA DE RAIOS X E CALIBRAÇÃO MULTIVARIADA - MORONA, FRANSLLEY (2016)
The organic matter (OM) and the Total Organic Carbon (TOC) content in the soil are of fundamental importance to agriculture and directly related to the system sustainability and to the cost of production. The determination of TOC content is commonly performed by soil analysis laboratories with Walkley Black method, which uses oxidation with potassium dichromate, highly carcinogenic reagent. The objective of this study is to develop a methodology for OM and TOC determination using Energy Dispersive X-Ray Fluorescence (EDXRF) and multivariate analysis, in order to minimize: the risks involved in handling chemicals, waste generated, costs and besides the analysis time. It were analyzed 152 soil samples from farms in the second and third Paraná plateau. Determinations were carried out by the conventional methods of WB and Gravimetry and by EDXRF. Spectral data from EDXRF were processed by partial least squares regression (PLSR) method for the development of predictive models. Van Bemmelen factor (relationship between OM and TOC) obtained with the OM content by gravimetric and TOC by WB was 4.37, higher than other factors cited in the literature, indicating the largest state of OM decomposition in the studied region. A global model for the determination of TOC was obtained using as reference the WB method, the average relative deviation was 16% for validation samples and R2 = 0.73. Were also obtained more specific models and for the watersheds of the Alto Ivaí, Alto Tibagi and the Afluentes do Médio Iguacú with average relative deviation of 13-22% with R2 between 0.53 and 0.90. The models obtained with the EDXRF data based on the gravimetric method showed better results, with a relative deviation average of 16% and R2 = 0.89 using the full spectrum and average relative deviation of 15% and R2 = 0.90 when using the scattering region. The paired t-test, applied to the validation samples, showed no significant difference in accuracy between EDXRF and WB methods and EDXRF and Gravimetric methods. The developed model considering only the scattering region proved its important relationship with the TOC and the OM. The cost estimate indicate the feasibility to replace WB by EDXRF for medium to high rate of analysis. The results equivalence suggests that EDXRF might be an alternative method for determining TOC with the advantages being faster analysis, nondestructive and accordance to green chemistry concepts.